Vegetarian diet and mental disorders: results from a representative community survey - Michalak Johannes; Zhang Xiao; Jacobi Frank (BMC, 2012)
Abstract Background The present study investigated associations between vegetarian diet and mental disorders. Methods Participants were drawn from the representative sample of the German Health Interview and Examination Survey and its Mental Health Supplement (GHS-MHS). Completely vegetarian (N = 54) and predominantly vegetarian (N = 190) participants were compared with non-vegetarian participants (N = 3872) and with a non-vegetarian socio-demographically matched subsample (N = 242). Results Vegetarians displayed elevated prevalence rates for depressive disorders, anxiety disorders and somatoform disorders. Due to the matching procedure, the findings cannot be explained by socio-demographic characteristics of vegetarians (e.g. higher rates of females, predominant residency in urban areas, high proportion of singles). The analysis of the respective ages at adoption of a vegetarian diet and onset of a mental disorder showed that the adoption of the vegetarian diet tends to follow the onset of mental disorders. Conclusions Vegetarian diet is associated with an elevated risk of mental disorders. However, there was no evidence for a causal role of vegetarian diet in the etiology of mental disorders.